Evolution of Mid‐latitude Density Irregularities and Scintillation in North America During the 7–8 September 2017 Storm. Issue 6 (21st June 2021) - Nishimura, Y.; Mrak, S.; Semeter, J. L.; Coster, A. J.; Jayachandran, P. T.; Groves, K. M.; Knudsen, D. J.; Nishitani, N.; Ruohoniemi, J. M.
Abstract: Using the University Navstar Consortium (UNAVCO) Global Positioning System (GPS) receiver network in North America, we present 2‐D distributions of GPS radio signal scintillation in the mid‐latitude ionosphere during the 7–8 September 2017 storm. The mid‐latitude ionosphere showed a variety of density structures such as the storm enhanced density (SED) base and plume, main trough, secondary plume, and secondary trough during the storm main and early recovery phases. Enhanced phase and amplitude scintillation indices were observed at the density gradients of those structures. SuperDARN radar echoes were also enhanced at the density gradients. The collocation of the scintillation and HF radar echoes indicates that density irregularities developed across a wide range of wavelengths (tens of meters to tens of kilometers) in the mid‐latitude density structures. The density gradients and irregularities were also detected by Swarm and DMSP as in‐situ density structures that disturbed the GPS signals. The irregularities were a substantial fraction (∼10%–50%) of the background density. The density irregularity had a power law spectrum with slope of ∼ −1.8, suggesting that gradient drift instability (GDI) contributed to turbulence formation. Both high‐latitude and low‐latitude processes likely contributed to forming the mid‐latitude density structures, and the mid‐latitude scintillation occurred at the interface of high‐latitude and low‐latitude forcing. Key Points: 2‐D distribution of GPS scintillation in the mid‐latitude ionosphere is presented, and the relation to SuperDARN echoes is studied The scintillation and density irregularities are related to SED base and plume, main trough, secondary plume, and secondary trough Density irregularities developed across a wide range of wavelengths from tens of meters to tens of kilometers